Reinforcing value and hypothetical behavioral economic demand for food and their relation to BMI. (April 2018) - Epstein, Leonard H.; Paluch, Rocco A.; Carr, Katelyn A.; Temple, Jennifer L.; Bickel, Warren K.; MacKillop, James
Abstract: Food is a primary reinforcer, and food reinforcement is related to obesity. The reinforcing value of food can be measured by establishing how hard someone will work to get food on progressive-ratio schedules. An alternative way to measure food reinforcement is a hypothetical purchase task which creates behavioral economic demand curves. This paper studies whether reinforcing value and hypothetical behavioral demand approaches are assessing the same or unique aspects of food reinforcement for low (LED) and high (HED) energy density foods using a combination of analytic approaches in females of varying BMI. Results showed absolute reinforcing value for LED and HED foods and relative reinforcing value were related to demand intensity ( r 's = 0.20–0.30, p 's < 0.01), and demand elasticity ( r 's = 0.17–0.22, p 's < 0.05). Correlations between demographic, BMI and restraint, disinhibition and hunger variables with the two measures of food reinforcement were different. Finally, the two measures provided unique contributions to predicting BMI. Potential reasons for differences between the reinforcing value and hypothetical purchase tasks were actual responding versus hypothetical purchasing, choice of reinforcers versus purchasing of individual foods in the demand task, and the differential role of effort in the two tasks. Examples of how a better understanding of food reinforcement may be useful to prevent or treat obesity are discussed, including engaging in alternative non-food reinforcers as substitutes for food, such as crafts or socializing in a non-food environment, and reducing the value of immediate food reinforcers by episodic future thinking. Highlights: Food reinforcement can be measured using an operant task or a hypothetical purchase task. The two measures of food reinforcement are correlated for both low and high energy dense foods. The measures are differentially related to demographic, BMI and psychological variables. The two measures provide independent or interactive contributions to predicting BMI.